2016
DOI: 10.1017/s0021859615001197
|View full text |Cite
|
Sign up to set email alerts
|

Planting pattern and irrigation effects on water status of winter wheat

Abstract: SUMMARYThe effects of planting pattern and irrigation on the soil water content, stomatal conductance, leaf relative water content, leaf water potential and leaf water use efficiency of winter wheat were investigated in North China during the 2008/09 and 2009/10 growing seasons. A field experiment was conducted using a randomized complete block design that consisted of three planting patterns: (i) a uniform row spacing of 25 cm, and alternating wide–narrow row spacing of 40 and 20 cm tested as (ii) flat and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Conversely, rainfall was insufficient in 2013/14, thus creating significant differences in RH between the planting patterns. The 3 years of experimental results showed that the twin row precision planting pattern increased RH and decreased soil temperature, which reduced soil water evaporation and maintained moisture levels (Wang et al 2016). Soil water content has a positive correlation with grain yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, rainfall was insufficient in 2013/14, thus creating significant differences in RH between the planting patterns. The 3 years of experimental results showed that the twin row precision planting pattern increased RH and decreased soil temperature, which reduced soil water evaporation and maintained moisture levels (Wang et al 2016). Soil water content has a positive correlation with grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as light, water, soil temperature and relative humidity (RH) can affect crop growth (Wang et al 2015). Wang et al (2016) demonstrated that furrow planting and irrigation had a significant effect on ET , WP and grain yield. Therefore, the microclimate of winter wheat farmland utilizing deficit irrigation and various planting patterns should be investigated by applying precision sowing.…”
Section: Introductionmentioning
confidence: 99%
“…Water stress induced a decrease in the leaf water status such as leaf relative water content (LRWC), leaf water potential (Lψ), leaf osmotic potential (Lπ), radiation use efficiency (RUE), and yield components and grain yield (Chowdhury et al., 2011) while increased the leaf abscisic acid (ABA) content (El‐Hendawy et al., 2019; Saradadevi et al., 2014). Nevertheless, considering the efficient use of limited water in NCP, the optimal deficit irrigation of winter wheat varies greatly, for instance, 60 mm (Fang et al., 2018), 75 mm (Ali et al., 2019), 135 mm (Wang et al., 2016), 165 mm (Dar et al., 2017) and 263 mm (Li et al., 2019), which there is no uniform optimal irrigation standard yet until now. The results of several investigators also indicated that irrigation frequency had great effect on winter wheat yield and WUE (El‐Hendawy et al., 2008; Pahlavan‐Rad et al., 2011; Tunio et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Row spacing is an important agronomic measure that determines plant spatial distribution, which affects plant canopy structure, and dry matter production; thus, row spacing ultimately influences biomass production (Mattera et al, 2013). Reasonable planting patterns are beneficial for improving the microclimate of farmlands and promoting the growth and development of crops (Wang et al, 2016). Han et al (2016) have shown that a wide-precision planting pattern results in higher winter wheat photosynthetic capacity compared with the conventional cultivation planting patterns.…”
Section: Introductionmentioning
confidence: 99%